Combined protein C and protein S deficiency with pregnancy - Chaudhari, Hemangi K.; Shah, Parmanand K.; Pai, Keshav R.; D’Souza, Natasha B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A 35 year old female patient, married since 8 years, G6P1L1SA4 was registered with our unit since 8th week of gestation. She was a known case of protein C and protein S deficiency diagnosed 7 years ago (thrombotic profile- protein C: 70% normal: 70-100%, protein S: 55% normal: 70/140%, AT-III: 116% normal 70/140%, factor V leiden: no mutation detected) which was detected on evaluation for her bad obstetric history. ACLA was also positive. She was started on injection low molecular weight heparin 0.6 mg s/c OD, in addition to continuing Tb. Aspirin 75 mg which had been started when the pregnancy was registered. Foleys induction was done at 39 weeks of gestation in view of previous LSCS with pre-eclampsia. Emergency LSCS was done in view of previous LSCS with non-progress of labour. Male child weighing 2.4 kg was born which is doing well. A patient having combined deficiency of both factors protein C and protein S is very rare. Anticoagulation therapy is the cornerstone in the management of patients with inherited coagulation defects.